Awakening time: a reflection about the Brazilian Puppeteers Network (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article is a report on the collective Rede de Bonequeiras Brasileiras (RBB). “Dollmakers” are understood to be artists who work with animation theater (dolls, objects, silhouettes/shadows and masks), in the most diverse activities, including producers, animating actresses, construction companies, among others. We are participants in this Network, and we bring reflections on how the collective emerged, the main actions carried out and possible directions. The main authors that permeate our reflections are Jacques Le Goff (2012), Maria Homem (2020), Grada Kilomba (2019) and bell hooks (2019).
Keywords: animation theater; puppetry; collective; feminism